INTEGRASI INFORMASI GEOGRAFIS PADA SISTEM IZIN MENDIRIKAN BANGUNAN KAWASAN PERDAGANGAN DAN JASA KOTA BANDAR LAMPUNG - Astria Hijriani; Nanda Adi Pratama (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
The Department of Housing and Settlements of Bandar Lampung City was formed based on the Regulation of the Lampung Province Number 8 of 2016 concerning the Formation and Arrangement of the Lampung Province Regional Apparatus. One of the activities carried out by the service is to make a Building Permit (IMB). Problems that are often experienced in spatial planning include irregular use of space and not in accordance with Building Permit and utilizing the use of space without regard to negative impacts on the surrounding environment. Especially in the trade and service area, most of Bandar Lampung City residents are engaged in industry, trade and services. In supporting the infrastructure of the development of activities in the field of Trade and Services, naturally effective and efficient development as a factor of economic growth for the region is needed. Therefore, as an element of service improvement in making permits to construct buildings, it needs tools in the form of technology. The technology in question is a website-based online licensing. With the advancement in technology, permit makers can access and submit licenses without being limited by distance, time and place. Then the integration of Geographic Information is applied to the Building Permit System for the Bandar Lampung City Trade and Services Area. In this system using the PHP programming language and Mariadb as the database. Testing using Black Box testing. In addition to the licensing process, this system also uses Google Maps Api as a geographic information feature in mapping building locations that have been submitted by permit makers. So that in addition to facilitating the applicant in the process of making permits, this system can also facilitate the Housing Settlement Office in monitoring and structuring the location of buildings in the Trade and Services area.